(untitled) (Web of Teachers: Inderscience Research, 2025)
This article deals with the issue of scientific and methodological justification of the requirements for the informatization of the content of education in the preparation of future teachers of technological education for professional activities based on digital technologies. This article can be used by those who deal with the problems of improving the training of future specialists for professional activities.